Peran Sistem Tata Kelola Lingkungan Berbasis Data Spasial dalam Perencanaan Pembangunan di Kawasan Urban - Yoga Ahmad Julian; Genius Umar (Journal of Current Research in Management, Policy, and Social Studies, 2025)
This study discusses the role of spatial data-based environmental governance systems in supporting development planning in urban areas, especially in DKI Jakarta. The main objectives of this study are to explore the contribution of spatial data in environmental planning, identify implementation challenges in urban areas, and evaluate the effectiveness of its use in addressing environmental problems. Through literature reviews and actual analysis, it was found that spatial data plays a role in detecting land cover changes, analyzing disaster risks, and mapping environmental damage accurately and in real time. Challenges such as limited infrastructure, lack of coordination between institutions, and lack of skilled human resources are still the main obstacles in implementing this system. Spatial data has proven effective in supporting evidence-based policy making at the urban level. Increased technological capacity, regulations that support data openness, and cross-sector integration are needed to encourage optimal use of spatial data in urban environmental.